Hubungan antara Tingkat Pengetahuan dan Status Gizi Ibu Hamil dengan Kejadian Anemia di Puskesmas Gatak Kabupaten Sukoharjo - Sukmaningtyas, Diana, Bejo Raharjo, SKM, M.Kes, Anisa Catur Wijayanti, SKM., M.Epid (2015)
Anemia towards pregnant women in puskesmas gatak sukoharjo regency in 2014 is 23%. Anemia during the pregnancy ensued death of the fetus in the uterus, abortion, natural deformity, BBLR, and hemorrhaging. Anemia indirectly causes morbidity and mortality of the mother and higher prenatal death. The purpose of this research to analyze the relation between the knowledge level and nutrient status of pregnant women towards anemia case in Puskesmas Gatak Sukoharjo Regency. The type of this research is observational research with case control design. The case population in this research is all anemia pregnant women found from July to September 2015, whereas the control population is the pregnant women who do not have anemia. The sampling selection in the case group is 30 peoples and the control group is 30 people using accidental sampling technique, whereas the statistical test uses chi square test. The result of this research shows that in variable of knowledge level, most of the respondents have high knowledge level that is 20 people (66,7%) in case group and 21 people (70%) in control group. While in variable of nutrient status, the respondent who has low nutrient status is 15 people (50%) in case group and 5 people (16,7%) in control group. The statistic result shows that there is no relation between the knowledge level (p= 0,781) and there is relation between nutrient status (p= 0,006; OR= 5,000; 95% CI= 1,510-16,560) and anemia case in Puskesmas Gatak Sukoharjo Regency.